Relationship between Knowledge Level and Community Attitude in Dengue Fever Prevention Behavior - Arief Romadhan; Putri Sari Wulandari; Rina Nofri Enis; Wahyu Indah Dewi Aurora; Esa Indah Ayudia (Journal of Medical Studies, 2024)
ABSTRACT Background: Dengue Hemorrhagic Fever (DHF) is an acute infectious disease caused by the Dengue virus which is transmitted by the Aedes aegypti mosquito. In cases of dengue fever, the symptoms often experienced by sufferers are sudden high fever, frequent bleeding, and if it is severe, they will experience shock and death. This research aims to determine the relationship between the level of knowledge and attitudes of the community in the behavior of preventing Dengue Fever in Jambi city in 2023. Methods: This research design used quantitative research with a cross-sectional design. The sample for this study comprised of residents from Kenali Besar, Paal V, and Payo Silincah Health Centers, totaling 86 respondents. Research instruments utilized questionnaires. The data were analyzed univariately and bivariately with the chi-square test. Results: Among the respondents, 41 individuals (47.7%) exhibited a good level of knowledge, 52 individuals (60.5%) demonstrated a positive attitude, and 37 individuals (43%) displayed good behavior. From the chi-square test, a p-value of 0.000 was obtained between the level of knowledge and preventive behavior towards dengue fever. A p-value of 0.000 was also obtained between attitudes and preventive behavior towards dengue fever. Conclusion: The level of knowledge and attitude of the community has a relationship with dengue prevention behavior in Jambi city. Keywords: dengue hemorrhagic fever (DHF); dengue fever; behavior; knowledge; attitude